Batch and Flow-Injection Spectrophotometric Determination of Paracetamol by Coupling with Diazotized 4-Aminoacetophenone - Baban, Sherwan Omer; Omer, Salah Kamal (Sulaimani Journal for Pure and Applied Sciences, 2016)
Simple, rapid, inexpensive, and sensitive batch and flow injection spectrophotometric methods have been proposed for determination of paracetamol in some pharmaceutical preparations. The proposed methods are based on the coupling reaction between paracetamol and diazotized 4-aminoacetophenone (DAAPH) in a basic medium using sodium hydroxide to produce a pinkish-red azo dye with maximum absorptivity at 500 nm. The reaction conditions and other analytical parameters were studied and optimized for both batch and flow injection procedures. The calibration graphs resulting from measuring the absorbance were linear over the ranges 5.0 - 30 and 25 – 180 µg/ml of paracetamol with relative standard deviations 0.26% and 0.18%, and detection limits (0.30, 0.35) µg/ml for batch and flow injection methods respectively. The proposed methods were applied to the analysis of paracetamol in some commercial pharmaceutical preparations. The observed results have a reasonable agreement with those obtained by an HPLC method as a standard certified method from Awamedica company for drug in Erbil-Iraq which based on British pharmacopeia…
Keywords: Spectrophotometric; Paracetamol; Flow injection; Diazotized 4aminoacetophenone Coupling reaction